REQUIREMENT ANALYSIS OF COMPUTER-BASED INSTRUMENTATION AND CONTROL SYSTEM FOR REAKTOR DAYA EKSPERIMENTAL - Restu Maerani; Tulis Jojok Suryono; Muhammad Subekti (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Developing and licensing of digital Instrumentation and control (I&C) system for nuclear power plant (NPP) are challenging especially for the new construction since digital technology are composite with a very high complexity of many integrated systems. National Nuclear Energy Agency of Indonesia (BATAN), who design Reaktor Daya Eksperimental (RDE), should prepare the documents to meet the licensing requirements of national regulator in this case Nuclear Energy Regulatory Agency of Indonesia (BAPETEN). BAPETEN’s chairman regulation No.6 year of 2012 is the first national requirement which state requirements related to design of computer-based system concerning on safety of power reactor that should be followed. Since BAPETEN only denotes requirements without state which code and standards to be used, therefore BATAN can add references from International Nuclear Energy Agency (IAEA) guidelines. In this paper, requirement document traceability is developed to determine which code and standards should be used to verify and validate the I&C computer-based system of RDE. The hierarchy of regulatory and utility requirements are developed to guide the design basis documentation. Developing requirements analysis of computer-based I&C system RDE are completed after determining the design requirements from the utility and regulatory requirements. This methodology will help the design engineers to follow the utility requirements by concerning to the production, and follow the regulatory requirements concerning the safety aspect.Keywords: Computer-based system, I&C System, Requirements analysis, Licensing, RDE